Equitable health: let's stick together as we address global discrimination, prejudice and stigma - Julie Babyar (BMC, 2018)
Abstract Tackling discrimination permanently in healthcare is not insurmountable. It is achievable. Discrimination is costly in lives, in healthcare delivery and waste, in human capital, in financial resource and even in healthcare improvement initiatives that do not adequately account for its impact. Healthcare must understand the underlying inequalities each faces from the start and tailor care toward equal health outcomes. Solutions have been offered and should be funded and evaluated. Additionally, a global plan to address discrimination and bias in healthcare must be consistent, accountable and be shaped around standardized tools and measures. The idea that an individual is better or more important than another has no place in today's world, particularly in health. Therefore, it is critical that each is provided his or her individual needs to achieve best outcomes. It is critical for healthcare to advance health equity. Global healthcare must do its part to be a team leader on this issue.